A Perception Model of Spam Risk Assessment Inspired by Danger Theory of Artificial Immune Systems - Zainal, K; Jali, MZ (Elsevier Science BV, 2024)
This present paper relates Danger Theory of Artificial Immune Systems, which has been introduced by Polly Matzinger in 1994 with the application in risk assessment. As to relate the concept of Danger Theory in risk assessment, a situation of determination severity level for detected Short Messaging Service (SMS) spam is applied. However, further testing is needed as to demonstrate the explained concept. Danger Model that based on the idea of the immune system is appear to be suitable as the fundamental principles and the most generic available solution as to assimilate its theory into the risk assessment environment especially that involve severe or hazardous impacts. (C) 2015 The Authors. Published by Elsevier B.V.